Japan's Low Inflation Conundrum - Thomas Mayer; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2022)
The paper analyses the reasons for Japan's persistently low inflation since the bursting of the Japanese bubble economy (low inflation conundrum). It is shown that Japan experienced a structural break from a high-growth period with relatively high inflation to a low-growth period with exceptionally low inflation since the early 1990s. We show based on a stylized accounting model, how funds are created in a country open to international capital flows by domestic savings, credit creation of banks and net capital inflows, being absorbed either by rising asset prices, newly issued bonds or more money being held. Government expenditure financed by government bond purchases of commercial banks is shown to be an important channel of money creation in Japan's post-bubble period. With the price level being assumed to be dependent on both goods with free market prices and goods with prices controlled by the government we show that inflation in Japan has been kept low by mainly three factors directly or indirectly influenced by the Bank of Japan: increased money holding of households and corporations, central bank-backed debt-financed price controls and net capital outflows.
Keywords: E31; E51; E58; 330; Japan; inflation; monetary policy; money supply; fiscal policy; asset prices inflation; balance of payments; price controls; subsidies